EFL STUDENTS’ PERSPECTIVES ON THE USE OF SMALLTALK2ME TO ENHANCE SPEAKING SKILLS: A STUDY OF UNDERGRADUATE LEARNERS - Fadlan Rambe; Ernita Daulay (Universitas Duta Bangsa Surakarta, 2025)
This research was initiated based on preliminary survey findings that highlighted the challenges faced by EFL students in speaking English, which subsequently guided the researcher’s focus. The primary objective of this study is to examine students’ perceptions of SmallTalk2Me as a digital tool for enhancing speaking proficiency. Employing a qualitative design, the study involved four students from a public institution in North Sumatra, who responded to open-ended questionnaires and participated in semi-structured interviews. Data were analyzed through thematic analysis, which revealed several significant themes: AI tools as scaffolding agents, confidence development in speaking, real-time feedback and error correction, social interaction with technology, and accessibility and flexibility of learning platforms. The findings indicated that SmallTalk2Me and similar AI-based applications were perceived as effective scaffolding agents, providing structured speaking practice, immediate feedback, and a supportive environment for trial and error. Participants reported noticeable improvements in pronunciation, fluency, confidence, and motivation. These results align with Vygotsky’s sociocultural theory, which underscores the role of scaffolding, mediation, and social interaction in second language acquisition. The selection of this theoretical framework was grounded in its relevance to the study’s objectives and its endorsement by the researcher’s advisor. Moreover, the study highlights that the integration of AI tools into language learning fosters learner autonomy and enhances speaking competence, particularly in contexts where interaction with native speakers is limited. The findings further emphasize the importance of emotional support and self-directed learning within digital speaking practice. Overall, SmallTalk2Me is shown to offer promising features that contribute to the development of students’ speaking abilities.